Keabsahan Jual Beli Menggunakan Perbuatan (Bai‘ al-Mu‘āṭāh) dalam Tinjauan Kaidah Fikih - Aisyah; Sudirman (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to find out and understand the validity of transactions without pronunciation, namely bai‘ al-mu‘āṭāh in reviewing the rules of fiqh. The type of research used is descriptive qualitative in the form of library research using a sociological approach to understand Islamic law, especially bai‘ al-mu‘āṭāh from a social perspective or community conditions. The results of this research show that bai‘ al-mu‘āṭāh is buying and selling carried out with certain movements or actions that show the agreement of both parties to the transaction. The validity of bai‘ al-mu‘āṭāh depends on the region and community conditions. In areas where transactions are commonly conducted through gestures without verbal expression, such as in almost all supermarkets in Indonesia where customers simply select items independently and pay at the cashier without any verbal exchange, bai‘ al-mu‘āṭāh is considered valid. However, in regions where transactions without verbal expression are uncommon, bai‘ al-mu‘āṭāh is not considered valid.